Effect of Pranayama Practice on Emotional Intelligence and Spiritual Intelligence in Nursing Students - Lida Abazari MSc; Aida Abazari MSc; Mohadese Emamgholi MSc; Neda Asadi PhD (SAGE Open Nursing)
Background and Aims Emotional intelligence (EI) and spiritual intelligence (SI) are critical for nursing students, enabling them to manage stressors effectively and deliver high-quality, compassionate care. Pranayama, a yogic breathing technique, is known to enhance psychological well-being. This study investigates the effects of ujjayi pranayama on EI and SI in final-year nursing students. Methods This quasi-experimental study was conducted among employed 46 final-year nursing students from Kerman University of Medical Sciences in southeastern Iran The participants were included in the study via a census method and were randomly assigned to either an intervention group ( n  = 23) or a control group ( n  = 23). The intervention group engaged in 15 min of guided pranayama daily for 20 consecutive days. The control group received no intervention during this period. Both groups completed the King Spiritual Intelligence Questionnaire, and the Schering Emotional Intelligence Questionnaire before and after the intervention. Descriptive statistics (frequency, percentage, mean, standard deviation) and analytical statistics (chi-square, independent t-test, and paired t-test) were used. Results EI significantly improved in the intervention group (from 100.17 ± 15.69 to 126.11 ± 16.81; p  = .02; Cohen's d  = 0.66), whereas the control group showed no improvement. No significant changes were found in SI ( p  > .05). Conclusions These findings suggest that short-term Ujjayi Pranayama practice is an effective, low-cost strategy to enhance EI in nursing students, potentially improving their readiness for emotionally demanding clinical environments. Incorporating such practices into nursing curricula may foster emotional resilience in future professionals.